Unraveling clinical experience occupational therapy student's perspective - Hernandez, Kathlene Anne V.; Erlyn A. Sana, PhD (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2012)
Clinical internship is one of the integral components of the Bachelor of Science in Occupational Therapy (BSOT) curriculum. It aims to provide opportunities for students to learn experientially, bridging the theories they learned in the classrooms and laboratories, with those of the actual workplace settings. Yet, we do not have a clear description of what clinical learning is based on student's experiences during training. This study utilized qualitative methods to explore the shared meaning of clinical learning amongst the students and to determine factors that affect it. The participants were four 5th year OT students enrolled at the University of Santo Tomas (UST) who (1) were regular students at the time of internship, and (2) have no failing mark in any of the affiliation centers. In-depth interviews and direct observations of actual rotations to describe clinical learning were done. Secondary data was also reviewed for data triangulation. Emerging themes and categories were then derived from these data. Results showed that actual clinical experience is considered as being a set of various teaching-learning experiences scheduled for the entire rotation, a challenge, and a learning experience. All interns reported to have experienced similar activities in different practice settings. The period of adjustment from being in the classroom to clinics, learning to manage time with all the duties and tasks assigned and being able to handle pressure or stress during internship are all interrelated factors contributing to a challenging clinical experience. Yet, it is still considered as a learning experience given that interns gained better understanding of the client, the self and the profession in general. The things they experienced during clinical internship are all real situations that contributed to their learning. Three major themes captured the perception of interns on learning during clinical internship. These are entering the real world, developing competence and confidence, and deeper understanding of OT. Entering the real world showed how students appreciate the day to day complexities of actual clinical setting, handling actual client and collaborating with their family and other members of the rehabilitation team. These experiences afforded to them contribute to the development of intern's competence and confidence. Being immersed in these activities, interns gained deeper understanding of the profession. This study further provides insights on the perceived factors affecting their learning in relation to self, supervisor, setting and other elements as well. Interns involved in this study reported relatively poorer quality experiences in some settings characterized by limited opportunities, resources and practice while rich experiences are associated with good supervision, variety of cases and promoting independence among others. The results of this study may be utilized by the institution, clinical supervisors and program developers. Institution may look at the positive and negative experiences of interns and use these to improve their clinical training program. Clinical supervisors may utilize the results to innovate their teaching styles to suit the needs of the interns. Furthermore, program developers can use this data for curricular change in order to improve the quality of students' learning experiences.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Maria Elizabeth M. Gargeda PTRP MHPEd, Reader/Critic; Melflor A. Atienza MD MHPEd, Member; Nomar M. Alviar MD MHPEd, Member; Jocelyn F. Agcaoili MSPT MHPEd, Member
Keywords: Occupational Therapy -- Curricula; Occupational therapy -- Study and teaching